Evaluasi Waktu Tunggu Resep Elektronik Pasien Rawat Jalan di Rumah Sakit X Kota Tangerang - Rangka, Febbyasi Megawaty; Laila, Zanatul; Novia, Jessica; Andriyani, Andriyani (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
An electronic prescription is a request for medication from a doctor for a patient by utilising software technology to the pharmacy. Prescription services have Hospital Minimum Service Standards (MSS), namely waiting time for non-recipe drugs ≤ 30 minutes and concise drugs ≤ 60 minutes. SPM waiting time at Hospital X Tangerang City for non-recipe drugs ≤ 8 minutes and compounded drugs ≤ 30 minutes. The purpose of the study was to evaluate the waiting time for electronic prescription drugs and the factors that influence it. Prospective descriptive research method with sampling data using random sampling technique on electronic prescriptions of outpatients for the period April - May 2022. The total population of January 2022 prescriptions was 750 sheets and the sample calculation using the Slovin formula was 261 prescription sheets. The results of the study of waiting time for non-recipe drugs totalling 213 prescription sheets with a time ≤ 8 minutes were 87 prescription sheets (40.85%), while 48 prescription sheets with a time ≤ 30 minutes were 19 prescription sheets (39.58%). The factor that led to the non-achievement of the SPM for waiting time for drugs was the stage of taking non-recombinant drugs (average 3.11 minutes).